Y = -3x + 5
5x - 4y = -3
5x - 4(-3x + 5) = -3
5x + 4(3x) - 4(5) = -3
5x + 12x - 20 = -3
17x - 20 = -3
+ 20 + 20
17x = 17
17 17
x = 1
y = -3x + 5
y = -3(1) + 5
y = -3 + 5
y = 2
(x, y) = (1, 2)
Answer:
https://www.caverna.k12.ky.us/userfiles/110/Classes/7142//userfiles/110/my%20files/study%20guide%20answer%20key%20(1).pdf?id=4059
Step-by-step explanation:
copy and past this pdf
Answer:
11/2
Step-by-step explanation:
6x−7=26
Step 1: Add 7 to both sides.
6x−7+7=26+7
6x=33
Step 2: Divide both sides by 6.
x= 11/2
105 × $8.72 = $915.60
$915.60 + $348 = $1,263.60
Mary paid $1,263.60 for the stock.